2011
DOI: 10.4236/psych.2011.25076
|View full text |Cite
|
Sign up to set email alerts
|

Mood States are Not Associated with BMI in Mentally Healthy Adults

Abstract: The relationship between Body Mass Index (BMI) and mental health has been widely investigated, and recent evidence has shown that overweight and obese individuals may be more vulnerable to the development of anxiety and mood disorders than individuals of a normal weight. This article examines the association between BMI and mood states of mentally healthy adults. BMI and Brunel Mood Scale (BRUMS) scores, and other demographic information, was collected from healthy adults over a six month period (N = 1621). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Overweight individuals have more possibilities of developing mental health difficulties (Titchener & Wong, 2015). The relationship between BMI and mental health has shown that individuals with higher BMI are more vulnerable to developing anxiety and mood disorders in comparison with those with normal weight (Wijk, 2011;Scott, McGee, Wells, & Oakley Browne, 2008). Depression measures were found to have the higher association with underweight and obese participants, and lower association with normal weight and overweight participants.…”
Section: Psychological Distressmentioning
confidence: 92%
“…Overweight individuals have more possibilities of developing mental health difficulties (Titchener & Wong, 2015). The relationship between BMI and mental health has shown that individuals with higher BMI are more vulnerable to developing anxiety and mood disorders in comparison with those with normal weight (Wijk, 2011;Scott, McGee, Wells, & Oakley Browne, 2008). Depression measures were found to have the higher association with underweight and obese participants, and lower association with normal weight and overweight participants.…”
Section: Psychological Distressmentioning
confidence: 92%
“…Τα υπζρβαρα άτομα ζχουν περιςςότερεσ πικανότθτεσ να αναπτφξουν προβλιματα ψυχικισ υγείασ (Titchener & Wong, 2015). Θ ςχζςθ μεταξφ ΔΜΣ και τθσ ψυχικισ υγείασ ζχει δείξει ότι τα άτομα με υψθλότερο ΔΜΣ είναι πιο ευάλωτα ςτθν ανάπτυξθ άγχουσ και διαταραχϊν διάκεςθσ ςε ςφγκριςθ με άτομα με ωυςιολογικό βάροσ (Scott, McGee, Wells, & Oakley Browne, 2008;Wijk, 2011). Επίςθσ, υπζρβαροι και παχφςαρκοι ωάνθκε να εμωανίηουν υψθλά ποςοςτά κατάκλιψθσ ςε ςφγκριςθ με άτομα ωυςιολογικοφ βάρουσ.…”
Section: ψυχολογικι ανάλυςθ για τθν παχυςαρκίαunclassified